Foraging behavior and microhabitats used by black lion tamarins, Leontopithecus chrysopygus (Mikan) (Primates, Callitrichidae) - Passos,Fernando de Camargo (1999)
Foraging in the Black Lion Tamarin (L. chrysopygus Mikan, 1823) was observed in the Caetetus Ecological Station, São Paulo, southeastern Brazil, during 83 days between November 1988 to October 1990. These tamarins use manipulative, specific-site foraging behavior. When searching for animal prey items, they examine a variety of microhabitats (dry palm leaves, twigs, under loose bark, in tree cavities). These microhabitats were spatially dispersed among different forest macrohabitats such as swamp forests and dry forested areas. These data indicated that the prey foraging behavior of L. chrysopygus was quite variable, and they used a wide variety of microhabitats, different of the other lion tamarin species.